METHODICAL DISCOURSE OF CONDUCTOR-CHOIR TRAINING TEACHER OF MUSICAL ART - Svitailo, Svitlana (Educological discourse, 2019)
The methodical aspects of preparing the future teacher of musical art during obtaining of higher education are studied. It is emphasized on the necessity to enrich the cognitive thesaurus of students, to develop a valuable perception of vocal and choral works, analytical thinking, possession of methods of learning vocal and choral works. The preparation of a teacher for work with choir collective or vocal band is opened. The students’ work on the analysis of vocal and choral works, selection of educational repertoire for schoolchildren of different age groups and enrichment of auditory experience has fundamental importance. At this stage, it is necessary to create students’ capability to make analysis (musical-theoretical, vocal-choral, performing) and interpretation of choral works, to compose it annotations, to collect and train exercises for developing the vocal-acoustic skills. The approximate vocal and choral analysis of the M. Lysenko Choir "Son" is presented; its general genre features are opened as a musical work intended for choral performance. Based on theoretical knowledge gained during the professional training, acquired methodical skills and independently working out specific choral works, the teacher of musical art can achieve the desired results in musical development of schoolchildren by vocal and choral singing.